Pengaruh Implementasi Safety Management System Terhadap Pelayanan Navigasi Penerbangan - Putu Krisna Surya Wardana; Dwi Lestary; Pangsa Rizkina Aswia (Politeknik Penerbangan Indonesia Curug, 2021)
This study aims to determine the effect of the Implementation of the Safety Management System (SMS) to Air Navigation Services at Perum LPPNPI of Banjarmasin Branch. This study used quantitative analysis in which the data collection method used a questionnaire, analysis of the SMS Gap Analysis Checklist and documentation studies while data processing was carried out by SPSS with a sample of 22 respondents and an error rate of 5% which is addressed to ATC personnel at Perum LPPNPI of Banjarmasin Branch. The SMS Gap Analysis Checklist was filled out by the Manager of Safety, Security and Standardization. The conclusion of this study is it is known that there was a significant relationship and influence between the implementation of SMS on Air Navigation Services with a coefficient value of 0.786 and a coefficient of determination of 62%. SMS Gap Analysis Checklist, the results showed that the SMS Implementation at Perum LPPNPI of Banjarmasin Branch was in stage I, namely SMS implementation planning. The results of the research were expected to be a source in evaluating the implementation of SMS and improving Air Navigation Service at Perum LPPNPI of Banjarmasin Branch.